Hubungan Asupan Protein Karbohidrat dan Zat Besi Dengan Stunting Pada Balita di Wilayah Puskesmas Gianyar 1 - Anzi, Ni Komang Yonik Liena; Kencana, I Ketut; Ambartana, I Wayan (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Stunting or often called stunting or stunting is a condition failure to thrive in children under five years old (toddlers) due to chronic malnutrition and repeated infections, especially during first 1,000 Days of Life (HPK) period, namely from fetus to child aged 23 months. Toddlers experiencing growth retardation characterized by short and very short physique are 2 main toddler nutrition problems in Bali. purpose of this study was to determine relationship between intake protein, carbohydrates and iron with stunting in toddlers in  Gianyar 1 Health Center area. Using research method using cross-sectional method presented in a cross table and then analyzed using statistical tests to determine the strength of the relationship and the direction of the relationship between variable. results this study are that there is relationship between intake of protein, kh , and iron (FE) on incidence stunting as indicated by the value α (0.05). With contingency coefficient value of 0.324 protein. Intake kh 0.354 and intake of iron (FE) 0.338. results this study it was suggested to families to pay attention amount intake toddlers both in womb and at birth and to carry out nutritional counseling at posyandu. Puskesmas always provide education about the dangers of stunting.